Emulator Rig for SOFC Hybrid Systems: Temperature and Power Control with a Real‐Time Software. Issue 6 (16th September 2013) - Caratozzolo, F.; Ferrari, M. L.; Traverso, A.; Massardo, A. F.
Abstract This work is based on the hybrid system emulator plant developed by the Thermochemical Power Group (TPG) of the University of Genoa. This rig is composed of a 100 kW microturbine coupled with high temperature fuel cell emulation devices. A real‐time model is used for components not physically present in the laboratory (solid oxide fuel cell (SOFC), reformer, anodic circuit, off‐gas burner, cathode blower). It is necessary to evaluate thermodynamic and electrochemical performance related to SOFC systems. Using an User Datagram Protocol (UDP) based connection with the control/acquisition software, it generates a hardware‐in‐the‐loop (HIL) facility for hybrid system emulation. Temperature, pressure, and mass flow rate at the recuperator outlet and machine rotational speed are measured in the plant and used as inputs for the model. The turbine outlet temperature (TOT) calculated by the model is fed into the machine control system and the turbine electric load is changed to match the model TOT values (effective plant/model coupling to avoid modifications on microturbine controller). Different tests were carried out to analyze hybrid system technology through the interaction between an experimental plant and a real‐time model. Double step and double ramp tests of current and fuel provided the system dynamic response.